Kelimpahan Kepiting Genus Uca di Kawasan Taman Nasional Bali Barat (TNBB) - Praftikayanti, Ni Putu Dian; Arthana, I Wayan; Indrawan, Gede Surya (Journal of Marine Research and Technology, 2024)
Mangroves are vegetation found in intertidal zones. The Uca genus of crabs is one of the crab genera that act as detritivores in the mangrove ecosystem. This research aimed to assess the abundance and male-to-female ratio of Uca genus crabs and the relationship between the abundance of Uca and the substrates found in the West Bali National Park (TNBB) mangrove area. The study was conducted from April to May 2023. The research locations were determined using purposive random sampling, with crab samples collected at three research stations. Data were analyzed using formulas for abundance index, diversity index, evenness index, dominance index, and gender ratio. Environmental factors such as temperature, salinity, pH, and substrate type were also measured. The research results revealed the presence of five species of Uca genus crabs: Uca annulipes, Uca tetragonon, Uca bellator, Uca coarctata, and Uca triangularis. The highest number of Uca tetragonon species was recorded at 18,57 individuals/m2, while the least abundant species was Uca triangularis, with only 2 ind/m 2 . The abundance index values were 17,6 ind/m 2 for station I, 14,2 and/m2 for station II, and 9,9 ind/m 2 for station III. The diversity index values ranged from low to moderate (0,67 – 1,07), with high evenness (0,61 – 0,98) and low to moderate dominance (0,35 – 0,52). The male-to-female ratio of Uca genus crabs indicated an imbalanced condition, where male Uca crabs were more dominant than females. At the three research stations, three substrate types were identified: station I had sandy clay substrate, station II had clayey sand substrate, and station III had sandy substrate.